Muhammad Ali - David, Keith 1956-; Squires, Buddy (PBS, 2021)
Examines the life of Muhammad Ali in and out of the boxing ring, covering his ties with the Nation of Islam, his political postions, including his refusal to be drafted during the Vietnam War, his role as a symbol of Black masculinity, and life after boxing
Originally produced for television broadcast in 2021
"This film contains graphic language. Viewer discretion is advised"--Sequence preceding title frames
Keywords: Ali, Muhammad -- 1942-2016; Dokumentarfilm; Boxen; Biografie; Ali, Muhammad / 1942-2016; Boxers (Sports) / United States / Biography; African American boxers / Biography; Political activists / United States / Biography; African American political activists / Biography; African American Muslims / Biography; Boxeurs / États-Unis / Biographies; Boxeurs noirs américains / Biographies; Activistes / États-Unis / Biographies; Activistes noirs américains / Biographies; African American political activists; African American Muslims; African American boxers; Boxers (Sports); Political activists; United States; Documentary television programs; Biographical television programs; Sports television programs; Nonfiction television programs; Television mini-series; Video recordings for the hearing impaired; Biography; Biographies; Documentaires télévisés; Biographies télévisées; Émissions sportives télévisées; Émissions télévisées autres que de fiction; Miniséries; Vidéos pour personnes handicapées auditives; Film; DVD-Video